Crop diversification increased household welfare in Afghanistan (2011-2017) - Hayatullah Ahmadzai; Oliver Morrissey (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2023)
Crop diversification is a farm level strategy to augment income, improve food security, and mitigate risks attributable to climate and market shocks. We use three-waves (2011/12 to 2016/17) of nationally representative repeated cross section surveys to study the impact of crop diversification on household welfare, measured by real adult equivalent consumption and food expenditure and dietary diversity, in Afghanistan. A multinomial endogenous switching regression (MESR) with instruments to correct for selection bias and endogeneity originating from both observed and unobserved heterogeneity is used to estimate average treatment effects of moving from one crop to two crops and then to three or more crops. Our analysis shows that crop diversification is a welfare enhancing strategy that increases household consumption, food security and dietary diversity. This holds for households in high and low conflict districts although the effect varies and households experiencing conflict tend to divert spending to food from other consumption spending. We also find a positive association between conflict, market related shocks and crop diversification, suggesting that households can adopt diversification to improve food security and mitigate the negative impacts of shocks by spreading risk through a wider production portfolio.
Keywords: I31; O13; Q12; Q34; O53; 330; Crop diversification; Household welfare; Multinomial endogenous switching regression(MESR); Conflict; Afghanistan